Chemokines as therapeutic targets for multiple sclerosis: a spatial and chronological perspective - Arimitsu, Nagisa Nakata; Witkowska, Alicja; Ohashi, Ayaka; Miyabe, Chie; Miyabe, Yoshishige (Frontiers in Immunology, 2025)
Multiple sclerosis (MS) is a chronic autoinflammatory disease of unknown origin, involving characterized by immune cell infiltration into the target tissue, central nervous system (CNS), resulting in local and/or systemic inflammation. The symptoms vary from gait disturbance, visual impairment and learning and memory impairment and are being managed with corticosteroid and/or immunosuppressive agents. However, several patients do not respond to these treatments, which can also elevate the risk of severe infections. Therefore, there remains an ongoing need to identify new therapeutic targets. MS exhibits distinctive pathology, clinical course, and treatment responses, suggesting the importance of targeting disease site-specific immune cells to mitigate immune system-induced inflammation, rather than employing broad immunosuppression. Chemokines and chemokine receptors play a crucial role in the pathogenesis of MS by recruiting immune cells to the CNS, leading to inflammation and demyelination. Therapies targeting chemokines have shown promising results in preclinical studies and clinical trials, but more research is needed to fully understand their mechanisms and optimize their efficacy.